Design Learning Media with an Open-Ended Problem Approach Using the Web to Improve Critical Thinking of Vocational Students - Noviana, Renra; Setiawan, Wawan; Wahyudin, Asep (Jurnal Guru Komputer, 2022)
Critical thinking skills must be provided through education, by developing critical thinking skills to make them better trained in solving various kinds of problems both in learning and outside learning. To improve critical thinking skills, an appropriate learning approach is needed, learning must be student-centered. This study aims to develop instructional media with an open-ended approach measure the improvements on students from the application of media and student responses to the media. This study uses a Comprehensive Life Cycle (SHM) methodology to develop media. One-group pretest post-test was used for the research design. media with an open-ended problem approach have been developed and get a percentage score of 86% or "very good" by experts on media testing and get a percentage score of 85% or "very good" by experts on material testing. The use of media with an open-ended approach can improve critical thinking skills with the increase in students' cognitive tests with the High Order Thinking Skill (HOTS) category questions with an increase in the average N-gain of students by 0.46 (which is in the "medium" category). Student responses to learning media get a percentage score of 75%.